Prevalence and public health risk of tuberculosis and nontuberculous mycobacteria in captive asian elephants (Elephas maximus Linnaeus) in Peninsular Malaysia - Yakubu, Yusuf (2015)
Tuberculosis (TB) remains a major public health problem worldwide with an estimated 9 million cases in 2013 and over 100 million deaths in the last century. The disease, caused by Mycobacterium tuberculosis, is estimated to infect one third of the world human population and was declared a global health emergency by the World Health Organization in 1993. Mycobacterium tuberculosis is an airborne multi-host pathogen capable of causing tuberculosis in humans and wide range of animal species. The disease has been reported among the captive Asian elephants (Elephas maximus) worldwide in the recent years with considerable conservation and public health threats. Infected elephants shed the pathogen in respiratory secretions thereby endangering other elephants and human in close contact. Few nontuberculous mycobacterium species (NTM) known to be opportunistic pathogens in humans have also been shown to cause fatal pulmonary disease in elephants. Nontuberculous mycobacterium infections in elephants have very poor prognosis and are often misdiagnosed for TB or other trivial respiratory problems. As effective treatment regimen for elephant TB and mycobacterial infection is yet to be established, the diseases continue to threaten the survivability of captive elephants and pose serious occupational hazard to humans especially elephant handlers and wildlife veterinarians. This study was conducted to investigate the epidemiology and public health hazards of tuberculosis and nontuberculous mycobacteria in captive Asian elephants in Peninsular Malaysia. The specific objectives were to detect and isolate M. tuberculosis and nontuberculous mycobacteria in trunk washes of captive Asian elephants, to determine the seroprevalence, incidence and risk factors for tuberculosis in captive Asian elephants, to determine prevalence and risk factors for tuberculosis among workers at elephant holding premises; and to investigate presence of novel virulence or survival adaptation genes in nontuberculous mycobacteria isolated from elephants. In the study, the proportion of elephant positive on molecular detection of M. tuberculosis complex (MTBC) in trunk washes was (16/28) 27.59% (CI:95%, 17.05 – 41.12). The MTBC detection rates by location were (2/2) 100% in facility D, (5/8) 65.50% in facility C, (4/9) 44.40% in facility E, (3/8) 37.50% in facility B and (2/31) 6.45% in facility A. Though M. tuberculosis could not be isolated, the proportion of elephants with nontuberculous mycobacteria isolates was (36/58) 62.07% (CI: 95%, 48.35-74.19). The isolation rates were (19/31) 61.29% in facility A, (4/8) 50.00% in facility B, (7/8) 87.50% in facility C, (1/2) 50.00% in facility D and (5/9) 55.56% in facility E. More than 70% of the NTM belong to three important NTM complexes, the M. terrae complex comprising M. terrae, M. nonchromogenicum, M. arupense, M. hiberniae and M. longobardum (31.48%); the M. fortuitum complex with M. fortuitum, M.peregrinum, M. septicum and M boenickei (20.36%); and the M. avium complex (MAC) comprising M. avium-intracellulare and M. colombiense (20.37%). The less frequently isolated spp. were M. asciaticum, M. agri, M.rutilum, M. mantenii, M. aurum, M. insubricum, M. wolinskyi, M. poriferae, M. flavescens, and M. gilvum (27.75%). The overall prevalence of elephant tuberculosis based on serological screening was (14/60) 23.33% (95% CI: 13.78–36.33). The prevalence elephant TB at first, second and third samplings were (10/51) 19.61%,(14/53) 26.42% and (9/37) 24.32% respectively. New cases of seroconversion were detected in two elephants resulting in an overall incidence of 2.6 cases per 100 elephant-years. Statistical analyses of putative risk factors showed that elephants with designated mahouts were at significantly higher risk of infection [p = 0.022, OR: 4.887 (95% CI: 1.258-18.248)]. Throughout the study, elephants in facility B and F were all seronegative. The overall seroprevalence of latent tuberculosis infection (LTBI) among wildlife staff was (37/149) 24.80% (95% CI: 18.29-32.70). Staff in facility E had the highest prevalence of (6/12) 50% while facility A had the lowest (13/70) 18.57%. The prevalence of latent tuberculosis among staff in facility B, C, D and F were (5/21) 23.81%, (5/20) 25%, (6/18) 33.30% and (2/8) 25% respectively. Univariable logistic regression showed risk of infection to be significantly associated with facility E staff [p = 0.024, OR: 4.385 (95% CI:1.217-15.801)], workers older than 30 years of age [p = 0.007, OR: 3.333 (95% CI: 1.351-8.227), mahouts [p = 0.034, OR: 3.778 (95% CI: 1.076-13.259)] and foreigners [p = 0.018, OR: 3.313 (95% CI: 1.214-8.086)].However, upon multivariable analysis only staff older than 30 years of age were significantly associated with the risk of LTBI [p = 0.010, OR: 3.315 (95% CI: 1.329-8.270)]. Correlation of tuberculosis among mahouts and elephants revealed minimal agreement with kappa value of 0.222. Investigation of novel virulence and survival adaptation genes in nontuberculous mycobacterium species (NTM) revealed presence of glycoside hydrolase family 76 gene in Mycobacterium fortuitum. The gene encodes for glycoside hydrolase family 76 protein, which is a mannosidase used for nutrient acquisition through the hydrolysis of mannose sugar. It has not been previously reported in M. fortuitum and phylogenetic analysis showed similarity of the gene with that of M.tuberculosis and Mycobacterium smegmatis. The study has provided significant information on the presence of M. tuberculosis and NTM in trunk washes of captive elephants in Peninsular Malaysia. Latent TB infection and potentially associated risk factors in elephants and wildlife staff have also been identified. The impending conservation and public health hazards necessitate the need for control strategies such as screening and quarantine of newly-acquired elephants, isolation of infected elephants and early treatment of confirmed cases. Periodic occupational hazards and training program need to be organized for wildlife employees. They should be provided with personal protective equipment (PPE) such as N95 mask, goggles and disposable aprons when dealing with TB infected elephants. There is the need to also initiate preemployment and annual tuberculin skin test (TST) in order to monitor the risk of infection among wildlife employees. From a global standpoint, health authorities need to recognize the public health risk of elephant TB and make its elimination an integral part of the WHO “STOP-TB partnership”programme.